Divergent corporates: Explaining mining companies divergent performance in health impact assessments. (December 2021) - Engebretsen, Rebecca Elisabeth Husebye; Brugger, Fritz
Abstract: Large resource extraction projects may give rise to significant environmental, social, and public health externalities. While the environmental impact of extractive projects is regularly considered prior to implementation, few countries have established legal requirements for other forms of impact assessments, including health impact assessments (HIA). Despite the lack of legal requirements, we find that some mining companies operating across Africa are going beyond what is required of them to consider the health impact of their operations. What explains this divergent behaviour? Using qualitative comparative analysis (QCA), we test key explanations of companies' self-regulating behaviour based on host country, home country or company related conditions. The results confirm that higher performance on HIA is not due to one or two single conditions but a combination of conditions that motivate mining companies to go beyond what is required by them. Our theory-testing contributes to the larger literature discussing companies' propensity to self-regulate. It offers a first step in testing relevant explanations for companies' self-regulatory behaviour in the HIA space, and offering an empirical foundation for future studies wishing to either scale up or scale down to add further granularity to this question in the future. Highlights: Health impact assessments (HIA) represent emerging yet unregulated practise in the extractive sector. HIA practises vary considerably amongst extractive mining firms across Africa. Qualitative comparative analysis (QCA) to study drivers of companies' divergent performance. In the absence of law and regulation, companies likely to self-regulate if certain conditions prevail.